Hypothesis: Can drug-loaded platelets be used as delivery vehicles for blood-brain barrier penetration?. (April 2019) - Kola, S.M.; Kumar, P.; Choonara, Y.E.; du Toit, L.C.; Pillay, V.
Abstract: Neurovascular conditions are disorders associated with the blood vessels of the brain that are extremely difficult to treat successfully due to the selectivity and fastidious nature of the blood- brain barrier. Consequently, the efficacy of the pharmacological treatments for these conditions are greatly reduced thereby resulting in large amounts of neurovascular-related morbidity and mortality. Platelets are an important component of blood that actively respond to neurovascular distress in the body. Recent research has proven the effectiveness of platelets as drug delivery vehicles, during circumstances where the body naturally elicits a platelet response. This hypothesis highlights the theoretical use of platelets as drug delivery vehicles, able to penetrate the blood-brain barrier, for the treatment of two neurovascular conditions; glioblastoma multiforme and ischemic stroke. The success of the hypothesised system may lead to the development of a novel and extremely necessary delivery mechanism.